An improved braking control method for the magnetically levitated TMP with a fast transient response. (February 2018) - Mao, Kun; Liu, Gang
Abstract: In the vacuum application based on the turbo-molecular pump (TMP), the pump rotor has to be stopped completely to prevent the blade from the air impact before trapping air into the vacuum chamber. However, due to the vacuum environment and high speed, the TMP braking process lasts much longer than that of the high-speed rotating machinery in the air. Particularly, the active magnetic bearings, which have been widely used in the TMP, eliminate the bearing friction resistance. In this case, the traditional electric braking method based on a non-controllable rectification cannot stop the rotor efficiently. Hence, a novel braking control method for the magnetically levitated TMP with a fast transient is proposed. When the TMP runs at high speed, it works like the traditional braking method, but with a temperature close-loop control, which is used to prevent the stator from overheat with the maximum current. Meanwhile, in the low speed range, the power switches of the inverter are controlled specifically to increase the DC-bus voltage. Thererfore, the barking current could be remained at a high level to reduce the braking time. At last, the proposed braking method is verified on a magnetically levitated TMP with 4100L/s pumping speed. Highlights: The traditional and improve braking method of the magnetically levitated turbo-molecular pump are analyzed. An improved braking method is proposed to reduce the braking time via active controllable rectification method. The temperature closed-loop control is also introduced to make full use of the water cooling machinery.